Table of Content - - (Journal of Arabic Language Sciences and Literature, 2025)
Table of Content: • A semiotic analysis of the Qur’anic verses concerning aggression: semantic, rhetorical, and phonetic perspectives Asst-Prof. Asmaa Wajeh Younis • The Value of Pre-Islamic Poetry in the Book of Bahjat Al-Majalis and Uns al-Majalis by Ibn Abd Al-Barr Al-Qurtubi (368-463 AH) Asst-Prof. Jamal Ali Ghidan • The Eloquence of Abu Bakr al-Siddiq’s Discourse: His Inaugural Caliphate Sermon as a Model (An Analytical Study) Dr. Jamil Hussein Ayyash • The Poetic Maqama and the Sana’ani Maqama: A Comparative Analytical Study of Narrative Structure and Rhetorical Patterns Ms. Thanaa Ayman Jumaa • Space formation and the power of the mask in the shrines of Badi Al-Zaman, A semiotic reading Dr. Ali Ezzi Qaid • The Linguistic Errors in Commercial Signs in the Southern Region and the Capital of the Kingdom of Bahrain: A Descriptive and Analytical Study Asst-Prof. Maha Fahed Abouhamra ,Asst-Prof. Ibrahim Suliman Ahmed, Mr. Mohamed Jaafar Hasan Ali Juma • The Desert in Pre-Islamic Poetry: A Perspective on Content and Art Mr. Ismaael Abd-Alrhman Waked